Documentation of Subtype C HIV Type 1 Strains in Argentina, Paraguay and Uruguay. - Carrion, G. (2004)
HIV subtypes B, F, and BF recombinants have been previously reported in South America. This report describes the presence of HIV-1 subtype C infection in the countries of Argentina, Uruguay, and Paraguay dating back to at least 1999. Surveillance for uncommon non-B/non-F subtype viruses circulating in South America has been conducted in samples obtained from nine countries. Peripheral blood mononuclear cells (PBMC), dried filter paper (FP), and fresh blood (FB) samples were collected from HIV-positive patients from Ecuador, Colombia, Venezuela, Peru, Chile, Bolivia, Argentina, Uruguay, and Paraguay. From a total of 2962 HIV seropositive samples examined during a 9-year period (1995-2003), only 11 (0.4%) were found to be infected with non-B/non-F HIV variants. Eight of these 11 strains were determined to be subtype C by heteroduplex mobility assay (HMA). Five of these 8 strains were further characterized by sequencing and phylogenetic analysis of the protease (Pro) and reverse transcriptase (RT) region of the genome and two were sequenced full length. One of the strains was found to be a unique BC recombinant. The spread of a third subtype of HIV, subtype C, should raise the question of its potential future role in the HIV epidemic in this region.